2013
DOI: 10.1007/s11746-013-2252-x
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Oryzanols of North American Wild Rice (Zizania palustris)

Abstract: γ-Oryzanol, a natural mixture of ferulic acid esters of triterpene alcohols and sterols, are an important bioactive components present in rice bran oil. In light of the recent increase in the popularity of wild rice among consumers, and the possibility of a direct relationship between γ-oryzanol composition and its bioactivity, the oryzanol profile of major wild rice (Zizania palustris) grown in North America was studied and compared to regular brown rice (Oryza sativa L.). A total of twenty-three γ-oryzanol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
(33 reference statements)
0
25
0
Order By: Relevance
“…In our study, sitosteryl ferulate (marker 125) is also a CM for wild rice, which is observed as having a higher intensity in wild rice coming from Canada than originating from USA. In the literature, profiles of individual steryl ferulates including sitosteryl ferulate in wild rice have been reported to be location dependent . The approach applied in this study can also distinguish different types of wild rice from different origins mainly based on compounds other than steryl ferulates.…”
Section: Resultsmentioning
confidence: 98%
“…In our study, sitosteryl ferulate (marker 125) is also a CM for wild rice, which is observed as having a higher intensity in wild rice coming from Canada than originating from USA. In the literature, profiles of individual steryl ferulates including sitosteryl ferulate in wild rice have been reported to be location dependent . The approach applied in this study can also distinguish different types of wild rice from different origins mainly based on compounds other than steryl ferulates.…”
Section: Resultsmentioning
confidence: 98%
“…The composition of individual γ‐oryzanols was similar among the wild rice samples but significantly different from those of the regular BR. In addition, the amount of γ‐oryzanol in wild rice was greater than those of regular BR (Aladedunye, Przybylski, Rudzinska, & Klensporf‐Pawlik, ). In another study, BR was found to contain 1.5 mg/g GABA and 0.38 mg/g γ‐oryzanol.…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…In Figure , gluconic acid, a glucose oxidation product ( m/z 195.0), is seen to be localized in the embryo of G02, G38, H24, H34, K11 and T05 rice varieties. The multiple components of γ ‐oryzanol are made up of the esters of triterpene alcohol ferulates and sterol ferulates . Two of the major γ ‐oryzanol components of the rice bran oil such as cycloartenyl ferulate (oryzanol A, m/z 601.5) and 24‐methyl cycloartenyl ferulate (oryzanol C, m/z 615.5) were mapped along the bran region of the rice varieties.…”
Section: Resultsmentioning
confidence: 99%
“…The multiple components of γ-oryzanol are made up of the esters of triterpene alcohol ferulates and sterol ferulates. 26,27 Two of the major γ-oryzanol components of the rice bran oil such as cycloartenyl ferulate (oryzanol A, m/z 601.5) and 24-methyl cycloartenyl ferulate (oryzanol C, m/z 615.5) were mapped along the bran region of the rice varieties. Oryzanol distribution is more pronounced in the T05 rice variety than the other rice landraces.…”
Section: Distribution Of Embryo-specific Moleculesmentioning
confidence: 99%